Integrating Entrepreneurial Ecosystem into Engineering Education: Driving Regional Economy in Tier-2 Cities - Kulkarni, Nitin; Shettar, Ashok; Atre, Madhusudan V. (Journal of Engineering Education Transformations, 2016)
Industry expectations from the young engineering graduates are changing rapidly. There is also a growing need for employing a large number of graduates. This is particularly important in several Tier-2/3 cities in India where a large majority of students graduate in engineering hoping to make a career. Except for a few top institutes in the big cities, most of the engineering institutions are in the Tier-2 cities where there are hardly any industries that can offer jobs to so many engineering graduates. This, results in a large number of graduates with little opportunities for employment, hence forcing them to move to the Tier-1 or Metro cities leaving behind an Intellectual void and a broken and dysfunctional social setup.With globalization of opportunities, being strong in technology basics alone isn’t just enough. Ability to think entre preneurially, dealing with ambiguity, thinking out of the box, intraprenurial approach at work, contributing to and helping to grow the local ecosystem, etc., are some of the competencies looked for by the employers. This paper shares some of the educational interventions undertaken at BVB College, Hubli to build business ecosystem on campus and to engage students as partners, to grow start-up culture.